Software and intelligent sciences new transdisciplinary findings - Wang, Yingxu; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
'This book discusses the transdisciplinary field known as software and intelligence sciences covering an array of developments in computer science, theoretical software engineering, cognitive science, cognitive informatics, and intelligence science'--Provided by publisher.
1. Convergence of software science and computational intelligence: a new transdisciplinary research field / Yingxu Wang -- 2. On abstract intelligence: toward a unifying theory of natural, artificial, machinable, and computational intelligence / Yingxu Wang -- 3. Hierarchies of architectures of collaborative computational intelligence / Witold Pedrycz -- 4. Challenges in the design of adoptive, intelligent and cognitive systems / W. Kinsner -- 5. On visual semantic algebra (VSA): a denotational mathematical structure for modeling and manipulating visual objects and patterns / Yingxu Wang -- 6. On cognitive computing / Yingxu Wang -- 7. On the system algebra foundations for granular computing / Yingxu Wang, Lotfi A. Zadeh, Yiyu Yao -- 8. Semantic matching, propagation and transformation for composition in component-based systems / Eric Bouillet ... [et al.] -- 9. Adaptive computation paradigm in knowledge representation: traditional and emerging applications / Marina L. Gavrilova -- 10. Protoforms of linguistic database summaries as a human consistent tool for using natural language in data mining / Janusz Kacprzyk, Slawomir Zadrozny -- 11. Measuring textual context based on cognitive principles / Ning Fang, Xiangfeng Luo, Weimin Xu -- 12. A lexical knowledge representation model for natural language understanding / Ping Chen, Wei Ding, Chengmin Ding -- 13. A dualism based semantics formalization mechanism for model driven engineering / Yucong Duan -- 14. Exploring the cognitive foundations of software engineering / Yingxu Wang, Shushma Patel -- 15. Positive and negative innovations in software engineering / Capers Jones -- 16. On the cognitive complexity of software and its quantification and formal measurement / Yingxu Wang -- 17. Machine learning and value-based software engineering / Du Zhang -- 18. The formal design model of a telephone switching system (TSS) / Yingxu Wang -- 19. The formal design model of a lift dispatching system (LDS) / Yingxu Wang ... [et al.] -- 20. A theory of program comprehension: joining vision science and program comprehension / Yann-Ga$1#0< (BGu{u2968}{u296E}euc -- 21. Requirements elicitation by defect elimination: an Indian logic perspective / G. S. Mahalakshmi, T. V. Geetha -- 22. Measurement of cognitive functional sizes of software / Sanjay Misra -- 23. Motivational gratification: an integrated work motivation model with information system design Perspective / Sugumar Mariappanadar -- 24. Supporting CSCW and CSCL with intelligent social grouping services / Jeffrey J.P. Tsai ... [et al.] -- 25. An enhanced Petri net model to verify and validate a neural-symbolic hybrid system / Ricardo R. Jorge, Gerardo R. Salgado, Vianey G. C. Schez -- 26. System uncertainty based data-driven knowledge acquisition / Jun Zhao, Guoyin Wang -- 27. Hierarchical function approximation with a neural network model / Luis F. De Mingo ... [et al.] -- 28. Application of artificial neural computation in Topex waveform data: a case study on water ratio regression / Bo Zhang, Franklin W. Schwartz, Daoqin Tong -- 29. A generic framework for feature representations in image categorization tasks / Adam Csapo ... [et al.].s
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed April 22, 2012).
Keywords: Computational intelligence; Computer software; Autonomic systems; Autonomous systems; Granular computing; Hybrid man-machine systems; Intelligent software engineering; Denotational vs. analytic mathematics; Mathematical models of the brain and mind; Real-time process algebra (RTPA).; Cognitive informatics; Intelligent behavioral foundations of software; Neural informatics; Theories for computational intelligence